Physiological and antioxidant mechamisms to overcome water stress on grafted peppers - Gara-Padilla, Yaiza; Gisbert-Mullor, Ramón; López-Serrano, Lidia; López-Galarza, Salvador; Calatayud, Ángeles (SEBP/SPFV, 2022)
Among abiotic stresses affecting crops, water scarcity rises as a major problem in many parts of the world, causing important losses in crop yield and productivity every year (Ashraf, 2010; Farooq et al., 2009; Mastrangelo et al., 2012). Grafting emerges as a sustainable technique that can be used to face this threat, particularly in Solanaceae species, usually cultivated in areas suffering from water starvation (Fullana-Pericàs et al., 2020; Kumar et al., 2017; Rouphael et al., 2018). Little has been published about the processes underlying grafted plants tolerance to water stress, especially in pepper plants. This work aimed to unravel several physiological and antioxidant mechanisms responsible for tolerance in pepper grafted plants under water stress.